1993
DOI: 10.1128/iai.61.12.5237-5244.1993
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Ileal symbiont intracellularis and porcine proliferative enteritis

Abstract: The relationship between Ileal symbiont (IS) intracellularis, formerly known as a Campylobacter-like organism, and porcine proliferative enteritis (PE) was studied by use of pigs with experimentally transmitted PE. Twenty one pigs were experimentally inoculated with homogenized ileal mucosa from a pig that died with PE, and 7 were maintained as uninoculated controls. Fecal samples were collected, and pigs were necropsied weekly postinoculation. Light microscopy and electron microscopy were used to examine tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Experimental challenge studies have demonstrated that serological results correlate well with shedding of L. intracellularis and clinical and histological evidence of PE 5,12–14 . Good correlations between serology and the duration of positive PCR results were also shown in this study; however, the predominantly subclinical population used in this study did not show strong correlations between serology and clinical scores.…”
Section: Discussionsupporting
confidence: 62%
“…Experimental challenge studies have demonstrated that serological results correlate well with shedding of L. intracellularis and clinical and histological evidence of PE 5,12–14 . Good correlations between serology and the duration of positive PCR results were also shown in this study; however, the predominantly subclinical population used in this study did not show strong correlations between serology and clinical scores.…”
Section: Discussionsupporting
confidence: 62%
“…Nucleus herds belonging to major breeding companies experienced a high rate of infection with the disease. The infection of pigs with L intracellularis can occur over a wide age range; pigs nearly three months old have become infected by an oral challenge (Jones and others 1993b). The infection can persist in individual pigs for at least 10 weeks, with large numbers of L intracellularis being readily detectable in faeces during the same period (Smith and McOrist 1997).…”
Section: Discussionmentioning
confidence: 99%
“…L. intracellularis also infects pigs sub-clinically, without clear clinical signs but still resulting in reduced growth performance. Its worldwide distribution and high prevalence have been recognized since the initial characterization of this pathogen in the early 1990s and L. intracellularis is reported to affect 57–100% of herds, globally [1] , [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%